Determinação de propriedades volumétricas e de transporte de diferentes tipos de carboidratos em meio aquoso - Ferreira, Ailton Freitas Balieiro (2018)
Carbohydrates, historically, are source of energy for humans, however, they don’t useful only for energetic functions. For example, glucose, galactose and lactose have been used in the removal neurotoxic compounds of the brain in patients suffering from Alzheimer’s and, in the pharmaceutical industries, along with other compounds, are used as drug excipients and aid gastrointestinal treatments. From these characteristics and applications, experimental data of density (ρ), speed of sound (u), and dynamic viscosity (η) of D-glucose, D-galactose and D-lactose in aqueous medium have been determined at different concentrations (0 to 3.7 mol·kg-1) and in temperatures T = (293.15 to 343.15) K. Posteriorly, inherent properties of the interactions in the medium, such as apparent molar volume (Vmapp), standard molar volume (Vm0), apparent molar isentropic compression (), standard molar isentropic compression (Km0) and other derivated thermodynamic properties were calculated, with the purpose of understanding the behavior of the intermolecular interactions of these carbohydrates in aqueous solution, since they are important for biology, pharmacy, chemistry and medicine. The results showed that carbohydrates are influenced by orientation of hydroxyl group (OH–), since they presented different values for the three measured properties, especially galactose and glucose isomers, due to mutarrotation that glucose suffers in aqueous medium, causing conformational change in its structure. Furthermore, the positive values found for demonstrate that solute-solvent interactions are stronger than solute-solute interactions, and the slight decreases presented for this property suggest that, at some times, there is smaller packing intensity among the molecules present in the mixture as they seek to accommodate. The behavior of Kmapp is characterized by an increase in the compressibility of the carbohydrate molecules in relation to water due to the strong hydrophilic interactions between solute-solvent. In the solute-solvent interactions, it was observed that the hydrophilic interactions occurring between groups containing the OH–, glycosidic bond and water were predominant to determine the behavior of Km0 and Vm0 of all evaluated systems.